Women's Mental Health and Wellbeing in the Interconception Period. Issue 6 (November 2021) - Leiferman, Jenn A.; Jewell, Jennifer S.; Huberty, Jennifer L.; Lee-Winn, Angela E.
Abstract: Purpose: Promoting women's health during the interconception period is critical for the health of future pregnancies. Methods: This was a cross-sectional study to better understand interconception mental health and wellbeing using a convenience sample of women recruited on social media who completed an online survey. Results: Women who participated in the survey ( N = 146) were 1 to 4 years since last pregnancy, primarily non-Hispanic White (81.2%), with an average age of 30 years (SD = 5.0; range = 19-47 years); 20% were insured by Medicaid. Depression, anxiety, stress, social support, mindfulness, and resilience were assessed. Approximately 22.9% reported depressive symptomatology, 18.8% symptoms of anxiety, 6.5% high stress, and 52.9% moderate stress. These patterns differed across years after giving birth, with percentages peaking for depressive symptoms during the first to second year (χ 2 = 9.81, p = 0.007), and anxiety symptoms peaking after the third year (χ 2 = 7.28, p = 0.026). Women reported moderate scores on wellbeing measures, with resilience scores decreasing as years since last pregnancy increased ( F = 3.24, p = 0.042). Less than 25% reported that a provider discussed depressed mood during the interconception period. Clinical Implications: Our findings revealed high prevalence and temporal patterns of depressive and anxiety symptoms during the interconception period, identifying a need for nurses to continue to follow-up with their patients about mental health concerns well after the traditionally defined 1 year postpartum. Further investigation of women's mental health and wellbeing and their unique needs during the interconception period is warranted. Abstract : Many new mothers experience anxiety and depression during postpartum. The Centers for Disease Control and Prevention estimates 1 in 8 women report symptoms of depression after giving birth and over 50% are not treated. In this study, women during postpartum and up to 4 years after giving birth were recruited using social media to particpate in a survey about their physical and mental health. Findings are similar to national prevalence data on postpartum depression and anxiety. Nursing care during postpartum must include screening for depression and appropriate referral and treatment when identifed.